Hypolipidaemic Effect of Lycopene from Red Tomatoes (Solanum lycopersicum L.) and its Potential for the Prevention of Cardiovascular Diseases - Akinsola Akinyele O (Tropical Journal of Natural Product Research, 2024)
The Nutritional and therapeutic benefits of lycopene from red tomatoes and its products cannot be overemphasized. Therefore, this study aimed to evaluate the hypolipidaemic effect of lycopene in three different preparations of red tomatoes in hyperlipidemic rats. Forty male Wistar rats were used for the study. The rats were divided into four groups (A - D) of 10 animals each. Group A was used as the control and received basal home diet throughout the duration of the experiment. Groups B, C, and D were fed with hyperlipidemic diets for one month, followed by lycopene in three different preparations of red tomatoes (Raw tomatoes, Tomato juice, and Cooked tomatoes) for another one month. Body weight and growth rate of the rats were monitored. The serum lipid profiles of the rats after administration of the hyperlipidaemic diet as well as after treatment with red tomato preparations were determined following standard procedures. Results showed that lycopene reduced weight gain induced by hyperlipidaemic diet, increased faecal fat content, and significantly reduced hyperlipidaemia in rats. The cooked tomatoes had the greatest effect in lowering serum total cholesterol, low density lipoprotein, and increasing high density lipoprotein levels. This suggests that lycopene present in cooked tomatoes are more readily absorbed in the intestine and therefore achieve higher concentration in the blood. Based on the findings from this study, dietary red tomatoes rich in lycopene may play a significant role in weight reduction, and in lowering plasma cholesterol which directly or indirectly reduces the risk of cardiovascular diseases.